Analisis Struktur Sepeda Lipat IZI ARC 16 dengan Menggunakan Metode Elemen Hingga - Zainal Abidin; Panji Janatama Aryadi (Universitas Sriwijaya, 2021)
In terms of the truth of the power on the bike is very important because lately many people are using this folding bike. On this night, use element method until application is labor-intensive. Before the analysis of the meshing process on the frame. After that the analysis is nothing. In this analysis the voltage result is not the value of the yield strength value on the material. So it doesn't break the frame. In addition to voltage, there are also strains and reforms that occur in frames whose value is not too large frame undergoes elastic deformation, and the result of analysis of security value is at least 10.6. This is the power of matter smaller than the voltage that occurs. So it can be stated that the bike will be safe if enabled or times.